REFLECTIONS ON INCLUSION AND NON-COMPETITION STARTED IN SPORTS (Fiep Bulletin - online, 2016)
This survey aims to analyze the perception about sport initiation and pedagogical target, defined by inclusion and not competitiveness. The research sought to understand how the stigmatized children participate in sports activities with another students, how the teachers feels to attending an event without competitive purposes, and how they work inclusion activities in your schools. The initial hypothesis would be that the inclusion to kinds of children will succeed if this activities doesn't have competitive goals. With purpose of achieving the goals, the methodology adopted was deprived a quality survey developed through analysis of the references. This survey was based on axes: inclusion and sport with emphasis on not competitiveness. Besides, this research contains interviews with four teachers of futsal schools from Porto Alegre, with goal to verify the perception of teachers about the didactic not competitiveness, above verify which inclusion's practice adopted in their schools. The interviews were analyzed from analysis of speech. After analysis of dates, the results were: the teacher believe in inclusion through the activities not competitiveness, making up a differential, so, the person's value regardless of their skills or technical level. The teachers knows that events with this action, has helped in the participation of all, developing respect, social integration and self-esteem. We analyzed that practice of sport can have contribution to inclusion, recognition of diversity and decreased stigma.
Keywords: Initiation sport; Education; Inclusion.